2010
DOI: 10.12942/lrr-2010-5
|View full text |Cite
|
Sign up to set email alerts
|

Brane-World Gravity

Abstract: The observable universe could be a 1+3-surface (the “brane”) embedded in a 1+3+d-dimensional spacetime (the “bulk”), with Standard Model particles and fields trapped on the brane while gravity is free to access the bulk. At least one of the d extra spatial dimensions could be very large relative to the Planck scale, which lowers the fundamental gravity scale, possibly even down to the electroweak (∼ TeV) level. This revolutionary picture arises in the framework of recent developments in M theory. The 1+10-dime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
1,016
1
15

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 742 publications
(1,053 citation statements)
references
References 438 publications
(1,177 reference statements)
10
1,016
1
15
Order By: Relevance
“…For reviews of observational tests of GR and dark energy, see [182,183] and [264,265], respectively. A topic we do not discuss in great depth is brane-world gravity and cosmology, but reviews can be found in [266][267][268][269][270][271][272].…”
Section: Organization Of the Reviewmentioning
confidence: 99%
“…For reviews of observational tests of GR and dark energy, see [182,183] and [264,265], respectively. A topic we do not discuss in great depth is brane-world gravity and cosmology, but reviews can be found in [266][267][268][269][270][271][272].…”
Section: Organization Of the Reviewmentioning
confidence: 99%
“…Moreover, the correspondence between the theories on AdS and Minkowski bulks may be used to derive new results in mathematical physics, in particular, in the theory of special functions (see, for instance, [8] and references therein). The braneworld scenario (for reviews see [9][10][11][12]) offers a new perspective on the hierarchy problem between the gravitational and electroweak mass scales. The main idea to resolve the large hierarchy is that the small coupling of four-dimensional gravity is generated by the large physical volume of extra dimensions.…”
Section: Jhep11(2015)092mentioning
confidence: 99%
“…In this scenario, the dynamics of the early universe may be substantially altered by the presence of additional quadratic terms in the energy density, resulting from the brane tension, as well as by the effects of nonzero components of the bulk Weyl tensor, which both give contributions to the effective, four-dimensional, energy-momentum tensor. For general reviews of brane world gravity and resulting cosmologies, see [54][55][56][57][58][59][60][61][62] .…”
Section: Introductionmentioning
confidence: 99%